CALDERON'S POLICY ON EDUCATION IN MEXICO (2006 - 2012) AS MDGs PROGRAM'S ACHIEVEMENT AND LESSON ON EDUCATION - Sekar Arum Apriliani (2013)
This research conducted aims to disclose the policy under Calderon's Administration and to explain the implementation of his education strategies for Mexico. It jointly opens the cooperation from International Government, Non-Governmental Organization and many corporations. In doing so, the Millennium Development Goals (MDGs) of Primary Education interest would be achieved in 2015 and advanced. The linked theoretical framework of human capital of capabilities would be well-attached on education